Elevated Perspectives: Unraveling Cardiovascular Dynamics in High-Altitude Realms - Aggarwal, Kanishk; Pathan, Mayur Srinivas; Dhalani, Mayank; Kaur, Inder P.; Anamika, Fnu; Gupta, Vasu; Jayaraman, Dilip Kumar; Jain, Rohit (Current Cardiology Reviews, 2025)
High-altitude regions pose distinctive challenges for cardiovascular health because of decreased oxygen levels, reduced barometric pressure, and colder temperatures. Approximately 82 million people live above 2400 meters, while over 100 million people visit these heights annually. Individuals ascending rapidly or those with pre-existing cardiovascular conditions are particularly vulnerable to altitude-related illnesses, including Acute Mountain Sickness (AMS) and Chronic Mountain Sickness (CMS). The cardiovascular system struggles to adapt to hypoxic stress, which can lead to arrhythmias, systemic hypertension, and right ventricular failure. Pathophysiologically, high-altitude exposure triggers immediate increases in cardiac output and heart rate, often due to enhanced sympathetic activity. Over time, acclimatisation involves complex changes, such as reduced stroke volume and increased blood volume. The pulmonary vasculature also undergoes significant alterations, including hypoxic pulmonary vasoconstriction and vascular remodelling, contributing to conditions, like pulmonary hypertension and high-altitude pulmonary edema. Genetic adaptations in populations living at high altitudes, such as gene variations linked to hypoxia response, further influence these physiological processes. Regarding cardiovascular disease risk, stable coronary artery disease patients generally do not face significant adverse outcomes at altitudes up to 3500 meters. However, those with unstable angina or recent cardiac interventions should avoid high-altitude exposure to prevent exacerbation. Remarkably, high-altitude living correlates with reduced cardiovascular mortality rates, possibly due to improved air quality and hypoxia-induced adaptations. Additionally, there is a higher incidence of congenital heart disease among children born at high altitudes, highlighting the profound impact of hypoxia on heart development. Understanding these dynamics is crucial for managing risks and improving health outcomes in high-altitude environments.
Keywords: pathophysiology